A post operative complication of foramen of Winslow hernia with left to right herniation of the small intestine: An extremely rare case report. (2018) - Fujihata, Shiro; Kitagami, Hidehiko; Yamamoto, Minoru; Nonoyama, Keisuke; Suzuki, Ayumi; Tanaka, Moritsugu; Ishiguro, Hideyuki; Takiguchi, Shuji
Highlights: A foramen of Winslow hernia is rare and difficult to diagnose. We report a post operative complication of foramen of Winslow herniation from left to right. There are no previous reports of a foramen of Winslow hernia with this presentation. It has been thought that closure of the foramen is not necessary. However, as there are no reports about the complications due to closing the Foramen of Winslow, the foramen should be closed, whenever possible. Abstract: Introduction: A foramen of Winslow hernia (FWH) is a type of internal hernias. Generally, the contents of the hernia pass through the foramen of Winslow from right to left. The case presented in this report is very unusual, as the small intestine in the hernia passed through the foramen from left to right. Presentation of case: A 67-year-old woman developed a sudden abdominal pain 15 days after laparoscopic subtotal colectomy. Abdominal contrast-enhanced computed tomography (CT) examination revealed a FWH, and an emergency surgery was scheduled. The small intestine was found to be herniating from the cavity of the omental bursa through the foramen of Winslow, to the right side of the hepatoduodenal ligament, and was incarcerated. The incarcerated intestine was reduced, and the necrotic part of the intestine was resected. In addition, the foramen of Winslow and the cavity of omental bursa were closed to prevent relapse. Conclusion: To our knowledge, here we report the first FWH of which the contents of the hernia are herniated from left to right, in literature. Whether the Foramen should be closed or not requires discussion, however, we conclude that the foramen should be closed when possible, acknowledging previous reports and the present case.